New Evidence on Long-Term Effects of Start-Up Subsidies: Matching Estimates and Their Robustness - Marco Caliendo; Stefan Tübbicke (Institute of Labor Economics (IZA), 2019)
The German start-up subsidy (SUS) program for the unemployed has recently undergone a major make-over, altering its institutional setup, adding an additional layer of selection and leading to ambiguous predictions of the program's effectiveness. Using propensity score matching (PSM) as our main empirical approach, we provide estimates of long-term effects of the post-reform subsidy on individual employment prospects and labor market earnings up to 40 months after entering the program. Our results suggest large and persistent long-term effects of the subsidy on employment probabilities and net earned income. These effects are larger than what was estimated for the pre-reform program. Extensive sensitivity analyses within the standard PSM framework reveal that the results are robust to different choices regarding the implementation of the weighting procedure and also with respect to deviations from the conditional independence assumption. As a further assessment of the results' sensitivity, we go beyond the standard selection-on-observables approach and employ an instrumental variable setup using regional variation in the likelihood of receiving treatment. Here, we exploit the fact that the reform increased the discretionary power of local employment agencies in allocating active labor market policy funds, allowing us to obtain a measure of local preferences for SUS as the program of choice. The results based on this approach give rise to similar estimates. Thus, our results indicating that SUS are still an effective active labor market program after the reform do not appear to be driven by "hidden bias".
Keywords: J68; H43; C14; C26; L26; 330; start-up subsidies; policy reform; matching; instrumental variables